2020
DOI: 10.1680/jadcr.18.00239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polycarboxylate superplasticisers with various functional groups on the pore structure of cement mortar

Abstract: The air-entraining capabilities of polycarboxylate superplasticisers (PCEs) with different functional groups were systematically analysed. Using different molecular PCEs, the evolution process from bubbles in fresh cement mortar to pores in hardened cement mortar was investigated, considering their effects on mortar workability and mechanical performance. The results showed that PCEs with various functional groups have different air-entraining capabilities. PCEs with ester groups decreased the surface tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The test results illustrate that carboxylic acid groups are beneficial in decreasing the surface tension of the solution, while the introduction of amide and sulfonic acid groups increases the surface tension of the solution, with the most significant increase in PCEs with addition of sulfonic acid groups, a result that is consistent with the literature. 35…”
Section: Surface Tensionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test results illustrate that carboxylic acid groups are beneficial in decreasing the surface tension of the solution, while the introduction of amide and sulfonic acid groups increases the surface tension of the solution, with the most significant increase in PCEs with addition of sulfonic acid groups, a result that is consistent with the literature. 35…”
Section: Surface Tensionmentioning
confidence: 99%
“…From the test results of surface tension and fluidity, it can be found that the smaller the surface tension of the PCE solution, the better the dispersion retention performance, this is due to the PCEs incorporation leads to changes in the air-entraining capacity in the cementwater system, 35,56,57 the low surface tension solution will introduce more bubbles, the bubbles in the inter-particle Combined with the test results of surface tension, heat of hydration of cement, setting time and compressive strength of mortar, it is known that the different molecular structure of PCE, the hydration effect on cement is also different, in which the molecular structure of carboxylate group with high density, the chelating effect with Ca 2+ in cement is stronger, so as to delay the hydration of cement more, 58 and the addition of amide group will accelerate the hydration of cement is due to the amide group of the N atom can provide a lone pair of electrons, which will make the Ca 2+ , AL 3+ , and Mg 2+ ions accelerate the hardening of flocculation and promote the hydration reaction. 59,60 However, Sodium methacrylsulfonate showed the best promotion of hydration and setting, probably due to its low air attraction caused by its low surface tension, and the lesser introduction of air bubbles resulted in a reduced retarding effect on the cement.…”
Section: Working Mechanismmentioning
confidence: 99%
“…Sulfonic acid group. When a small number of sulfonic acid groups was used to replace the carboxyl groups in the main PCE chain, the fresh mortar with sulfonic acid group-containing PCE had a significantly increased or decreased air void of 5–6%, as shown in Figure 17 below [ 63 ]. As the sulfonic acid group gradually increased, the air-entrainment amount in the cement mortar gradually decreased because more sulfonic acid groups would lead to an increased concentration of PCE adsorbed on the cement particle surface.…”
Section: Factors Influencing Bubble Generation and Developmentmentioning
confidence: 99%
“…After the grafted ester group enters the side chain, PCE has a lower surface tension, which can significantly improve the air-entraining ability and change large bubbles into small bubbles. PCE with sulfonic acid groups inserted in the main chain cannot optimize the pore structure of concrete, with a large number of macropores still present in the hardened cement mortar [ 63 ]. Therefore, how to use the above experimental methods to optimize the PCE molecular structure is still worthy of further study.…”
Section: Factors Influencing Bubble Generation and Developmentmentioning
confidence: 99%
“…The FAC paste will rapidly lose fluidity or workability due to its excessive hydration rate, and greatly reduce its construction performance. Water reducing agents is a kind of important chemical admixture for Portland cement-based materials [24][25][26][27]. They can increase the workability of fresh concrete without additional water, or reduce the amount of water for a given fluidity [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%